Recent Progress in 3D Multimedia Research - Florencio, Dinei (Hot3D Report, 2010)
The first International Workshop on Hot Topics in 3D multimedia (Hot3D), was help in Singapore, in July 2010, in conjunction with the IEEE International Conference on Multimedia and Expo (ICME). Sponsored by four different IEEE societies, ICME is the IEEE flagship conference on Multimedia. Hot3D was a vibrant workshop, very well attended, with an impressive collection of papers covering several aspects of 3D multimedia. This report summarizes some of the results presented at the workshop.